Prostate biopsy and prostate cancer management in patients with haemophilia: The experience of French Haemophilia Treatment Centres. Issue 3 (24th February 2022) - Gautier, Philippe; Guillet, Benoit; Sigaud, Marianne; Claeyssens, Ségolène; Volot, Fabienne Genre; Chamouni, Pierre; Lienahrt, Anne; Frotscher, Birgit; Fournel, Alexandra; Castet, Sabine; Poumayou, Catherine; Gay, Valérie; et al.
Abstract: Background: Data are limited on prostate cancer (PC) management in patients with haemophilia (PWH). Aim: To describe PC screening and diagnosis, treatment modalities and bleeding complications in a group of unselected PWH followed at French Haemophilia Treatment Centres (HTCs) Patients and methods: PC screening, management and bleeding complications were retrospectively investigated at 14 French HTCs between 2003 and 2018. Results: Among> 1549 > 50‐year‐old PWHs, 73 (4.7%) underwent PC screening (median age 71.1 years; 67/6 HA/HB, 17/56 severe‐moderate/mild). At diagnosis, haematuria was infrequent. Prophylaxis was administered during 76/86 (88%) prostate biopsies (PB) ( n = 67 clotting factor concentrates, CFC; n = 9 desmopressin; n = 17 associated with tranexamic acid, TA). Bleeding (11/86, 12.8%) occurred mainly post‐prophylaxis (median delay: 7 days): haematuria (9/11, 81.8%), and rectal bleeding (2/11, 18.2%) including one major (1.2%). PC was confirmed in 50/86 PB and in two prostatectomy specimens (total n = 50 patients, n = 6 with only active surveillance). Surgery ( n = 28/44 patients) was managed with CFC. Fifteen patients had radiotherapy/brachytherapy, 10 had hormone therapy; CFC‐based prophylaxis was only prescribed for brachytherapy ( n = 2). Major bleedings occurred in 3/28 (10.7%) and 2/15 (13.3%) patients who underwent surgery and radio/brachytherapy, respectively. No bleeding risk factor was found. Conclusion: Our data indicate that PB requires prophylaxis for atleast 7 days, using CFC, desmopressin or TA in function of haemophilia severity. PC surgery should be considered at high bleeding risk. Long‐term post‐procedural CFC or oral TA could be discussed. Radiotherapy/brachytherapy also should be managed with prophylaxis (CFC or TA).